Hyphessobrycon togoi, a new species from the La Plata basin (Teleostei: Characidae) and comments about the distribution of the genus in Argentina - Miquelarena, Amalia María (2006)
A new species of the characid genus Hyphessobrycon is described from tributaries of the Río de la Plata and the Salado River system in middle-eastern Argentina. Hyphessobrycon togoi can be distinguished from all congeners, except H. langeanii Lima & Moreira, by the presence of a well-defined, round to horizontally oval humeral spot. Other diagnostic characters defining Hyphesso-brycon togoi are the possession of a short expanded maxilla with one large multicuspid tooth; premaxilla with an outer row of 3 small teeth, with 5 or 6 cusps, relatively apart from each other; inner series with 5 teeth that are distally broader, with numerous cusps (6-11) and overlapping each other; iv-v, 17-20 anal-fin rays; 31-36 scales on longitudinal series. Hyphessobrycon togoi is also distinguished by the presence of bony hooks on all fins of the mature males. Considerations about the distribution of the species of genus Hyphessobrycon in Argentina are included.